Preliminary Physico-Chemical Studies of Water Flow of Machna Annicut Dam, District Betul (M.P.) - Saluja, D.S.; Jain, Praveen (Asian Journal of Chemistry, 2010)
Betul, a district of Madhya Pradesh, is situated about 199 km,southeast of Bhopal. The need of water for irrigation and otherpurposes is met from Machna river, the lifeline of Betul city. Thisriver also caters to the drinking water needs of Betual city. Themonitoring of Machna Annicut dam water flow has been doneseasonally at Vivekanand Nagar, Betul. The samples were collectedfrom the upstream and downsteam of the flow path of the river atsix points. Water temperature, turbidity and conductivity were foundhigher in summer season. The pH, alkalinity, nitrate, chloride,fluoride, total hardness, Ca and Mg hardness, BOD and COD werefound higher in monsoon season. The study is aimed to assess thedegree of pollution of Machna Annicut dam water and its qualitystatus.